The Development of Augmented Reality Based Student Worksheet on Human Respiratory System Course to Improve Critical Thinking Skills of Junior High School - Maimuna, Siti; Wahyuni, Sri; Ridlo, Zainur Rasyid (Indonesia Emerging Literacy Education, 2024)
Objective: The development of augmented reality based student is used to improve the critical thinking skills of junior high school science students. This research aims to describe the validity, practicality and effectiveness of augmented reality based student worksheet oh Human Respiratory System course. Method: This research applies the ADDIE model was carried out at Jember’ 12 Junior High School and the data collection instruments used are observation sheets, validation sheets, student response questionnaires, and test assessment sheets. Results: The results obtained are the validity of the product is declared valid with a percentage of 92%, the practicality results are classified as practicaland the effectiveness results are very positive. N-gain results of 0.55 which is included in the moderate category. Novelty: Augmented reality-based student worksheet can be used in science learning as an alternative learning media to improve critical thinking skills of junior high school students.